2011
DOI: 10.1128/jcm.01426-10
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multiplex Real-Time PCR Diagnostic Assay for Identification and Differentiation of Mycobacterium tuberculosis, Mycobacterium canettii, and Mycobacterium tuberculosis Complex Strains

Abstract: Tuberculosis (TB) in humans is caused by members of the Mycobacterium tuberculosis complex (MTC).Rapid detection of the MTC is necessary for the timely initiation of antibiotic treatment, while differentiation between members of the complex may be important to guide the appropriate antibiotic treatment and provide epidemiological information. In this study, a multiplex real-time PCR diagnostics assay using novel molecular targets was designed to identify the MTC while simultaneously differentiating between M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…There is currently no single nucleic acid diagnostics target described in the literature that can unambiguously identify H. influenzae. As such, in this study, a number of gene targets, including ssrA and lepA and genes that have previously been described in the literature as suitable bacterial species specific molecular diagnostics targets, were evaluated in silico (26)(27)(28). A putative novel diagnostics gene target, smpB, selected and identified by the NADRL, was also evaluated in silico.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently no single nucleic acid diagnostics target described in the literature that can unambiguously identify H. influenzae. As such, in this study, a number of gene targets, including ssrA and lepA and genes that have previously been described in the literature as suitable bacterial species specific molecular diagnostics targets, were evaluated in silico (26)(27)(28). A putative novel diagnostics gene target, smpB, selected and identified by the NADRL, was also evaluated in silico.…”
Section: Resultsmentioning
confidence: 99%
“…These gene targets were chosen, as they are either present in all bacteria sequenced to date and/or have previously been demonstrated to be suitable as bacterial species-specific molecular-based diagnostics targets (26,28,36,37). Of these, only the smpB gene demonstrated sufficient in silico nucleotide sequence heterogeneity to allow for the design of an H. influenzae-specific diagnostic assay.…”
Section: Discussionmentioning
confidence: 99%
“…The novel diagnostic targets used in this study were identified by using in silico comparative genomic approaches previously described (22,23). All oligonucleotides used in this study were designed in accordance with previously reported guidelines (10,24).…”
Section: Methodsmentioning
confidence: 99%
“…The panel of MTC isolates, nontuberculosis mycobacteria (NTM), and other bacterial species used in this study (see Tables S1 and S2 in the supplemental material) was the same panel as that described in a previous study (23), with the addition of 47 MTC isolates provided by the National Reference Center for Mycobacteria, Borstel, Germany (characterized as described previously by Allix-Bé-guec et al [2]). All genomic DNA samples used in this study were isolated, quantified, and stored as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation